Firenze prima degli Uberti Il ceto dirigente fiorentino nell'XI secolo fra riforme diocesane e affermazione personale e familiare - Contessa, Maria Pia (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2023)
Along the 11th century florentine bishops attempted to reinforce the diocese. Their initiatives were supported by Hucpoldings, an illustrious kindred group born in Florence in the mid of the 9th century and spreaded over the Kingdom of Italy. Yet at that time some members of the group were still keeping important interests in the city and in its comitatus. Particularly, the aristocratic kinship known as Adimari had created a strong backing link with the florentine bishopric about the year one thousand. Inspired by their forefathers' political and cultural heritage, they alternately adapted carolingian patterns of social interaction to contemporary times and needs. In that way they perpetuated their lay leadership over the half of the century.